2021
DOI: 10.1101/2021.01.25.428055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BAG3 regulation of Rab35 mediates the Endosomal Sorting Complexes Required for Transport /endolysosome pathway and tau clearance

Abstract: The decline in proteostasis during aging is a major contributing factor to increased susceptibility to neurodegenerative diseases such as Alzheimer’s disease. Although dysfunction of the autophagy pathway is likely one of the contributors, emerging studies implicate that impairment of the endosome-lysosome pathway is also a significant factor in the pathogenesis of these diseases. Our lab was the first to demonstrate that BAG3 facilitates phosphorylated tau clearance through autophagy. However, we did not full… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 88 publications
(144 reference statements)
2
12
0
Order By: Relevance
“…It plays an essential role in maintaining proteostasis and serves a protective role against neurodegeneration [14][15][16]. Previously, we demonstrated that BAG3 plays an important role in regulating MAPT clearance through autophagy [17,18], and, more recently, we found that BAG3 also regulates ESCRT-mediated MAPT clearance [19]. These findings point to the importance of BAG3 in both autophagy and ESCRT-mediated pathways.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…It plays an essential role in maintaining proteostasis and serves a protective role against neurodegeneration [14][15][16]. Previously, we demonstrated that BAG3 plays an important role in regulating MAPT clearance through autophagy [17,18], and, more recently, we found that BAG3 also regulates ESCRT-mediated MAPT clearance [19]. These findings point to the importance of BAG3 in both autophagy and ESCRT-mediated pathways.…”
Section: Introductionsupporting
confidence: 51%
“…Constructs: lentiviral vectors: shBAG3 (5'-AAGGTTCAGACCATCTTGGAA-3'), scrRNA (5'-CAGTCGCGTTTGCGACTGG-3') in FG12 (with an H1 promoter) [21], or pHUUG with a U6 promoter (a generous gift of from Dr. C.Pröschel, University of Rochester) with and without GFP were used [19]. shSQSTM1 (5'-GAG GAA CTG ACA ATG GCC ATG TCC T -3') was prepared in FG12, and shNBR1 (5'-GCA TGA CAG CCC TTT AAT AGA-3') was prepared in pHUUG.…”
Section: Reagentsmentioning
confidence: 99%
“…BAG3, through its interaction with TBC1D10B supports the activation of Rab35 and recruitment of Hrs, which initiates ESCRT‐mediated endosomal tau clearance. Intrahippocampal expression of BAG3 in P301S mice increased the co‐localization of phospho‐tau with the ESCRT III protein CHMP2B and reduced the levels of the mutant human tau 144 . In summary, these studies indicate a close link between the protective function of BAG3 and tau clearance in an excitatory neuron preferential manner.…”
Section: Bag3 In the Nervous Systemmentioning
confidence: 60%
“…Intrahippocampal expression of BAG3 in P301S mice increased the co-localization of phospho-tau with the ESCRT III protein CHMP2B and reduced the levels of the mutant human tau. 144 In summary, these studies indicate a close link between the protective function of BAG3 and tau clearance in an excitatory neuron preferential manner. These findings highlight an important role of BAG3 in neuronal proteostasis and pathogenesis of AD, as well as other neurodegenerative diseases.…”
Section: Bag3 Functions In Admentioning
confidence: 68%
“…In another study of tauopathy mice, increased farnesyl transferase activity to translocate the Rhes GTPase to autophagic vesicles was associated with low tau hyperphosphorylation, while inhibition of Rhes promoted tau hyperphosphorylation [115]. Thus, GTPase-dependent autophagy effectively clears pTau [116] and impaired autophagy from low GTP levels or oxidative redox state would impair clearance of pTau.…”
Section: Of Tubulin Assembly Vesicle Transport and Protein Synthesismentioning
confidence: 97%